الأخطاء التعبيرية في المحادثة العربية لدى طلاب معهد المنار الحديث للتربية الإسلامية: Mistakes, Language Expression, Arabic Conversation - Ø£Ø²ÙˆÙŠØ±, Ø§Ù„Ø³ÙŠØ¯; Ø¹Ø¨Ø¯ Ø§Ù„Ø±ØÙ…Ù†, Ù…ØÙ…Ø¯ Ø²ÙƒÙŠ (Al-Ḍād Journal, 2019)
The aim of this paper is to address the issue of expression errors in the Arabic conversation among the students of Al-Manar Institute for Islamic Education. The students are assigned to practice Arabic with each other within the linguistic environment in which they are only allowed to speak Arabic. The aim of these language activities was to train students to speak in Arabic so that they could speak standard Arabic. Although they have spoken with their friends in Arabic they still make mistakes in language expression. The findings of this research show that most of them still use some words of Arabic that have different meaning with its original sense. For example, some students call their friend using "هُناَ" rather than "تعال" and they use "جَرِّبْ" instead of "دَعْنِي" if they ask a friend to see what they have in their hand. They said "خَلاَص" in terms of finishing work rather than using the past verb. These mistakes indicate that the students still face problems in using Arabic vocabulary in their daily conversation as they use Arabic based on Indonesian context.